Quantitative and Qualitative Analysis of Dental Caries among Different Age Groups of Patients in a Private Dental College Hospital, Chennai, India - Akshaya. K1 , Prathiba Ramani2 , Senthil Murugan. P3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dental caries is the major health disorder caused by the interaction of oral microbes on the dental hard tissues.Dental caries are multifactorial in nature of etiology and pathogenesis. According to WHO almost 36% ofthe population have dental caries. Thus the aim of the current study is to quantitatively and qualitativelyanalyse the prevalence of dental caries among different age groups of patients visiting Saveetha dentalcollege and hospital outpatient department services. All the cases reported between the month of June2019 to March 2020 for dental caries of different classes were chosen for this study. Data of patients wereretrieved from dental records. Data of patients with class I to class VI dental caries and root caries wereincluded and age, gender, tooth affected were analyzed, tabulated and was subjected to statistical analysis.From the data analysis through SPSS it is observed that, the overall incidence of dental caries were higheramong male patients (54.7%), between the age group of 15 to 30 years (45.4%) and was commonly seen inprimary and permanent posterior tooth.(72.6%). Within the limitations of the present study, dental caries hadmale predilection, predominantly between the age group of 15 to 30 years,Class 1 caries primarily reportedin the molars.